Flow behaviors of 22MnB5 steel at a high temperature. (10th April 2019) - Fei, Wei-Jie; Li, Hua-Guan; Li, Xuan; Li, Qi; Liu, Yong-Gang; Gu, Hai-Rong; Wang, Zhang-Zhong
Abstract: Flow behaviors of 22MnB5 ultra-high strength steel (UHSS) at different temperatures and strain rates were investigated using uniaxial tension tests. The variables of the Arrhenius model, which involved n, Q, α, and lnA, was calculated using a fifth order polynomial fitting method. At a strain of 0.1, the values of n, Q, α, and lnA were respectively 8.24579, 177.7588 kJ·mol −1, 0.00618 MPa −1, and 25.77352 s −1 . The results indicate that the change in rheological stress was inversely proportional to the change in temperature but was positively correlated with the change in strain rate. The new model reproduced the flow behaviors of this novel UHSS sheet well for a wide range of strain rates and temperature conditions.